TOTAL QUALITY MANAGEMENT IN THE IMPLEMENTATION OF ISLAMIC SCHOOL CULTURE AT SMP NEGERI 1 LABUHANHAJI TIMUR - Maulinas; Akmaluddin; Mayang Sari; Rahmatullah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to determine TQM planning in the application of Islamic schoolculture, the implementation of Islamic school culture and the constraints ofimplementing Islamic school culture at SMPN 1 Labuhanhaji Timur. This studyuses a qualitative descriptive approach by conducting observations, interviewsand documentation. The results of the research show that TQM planning iscarried out by forming a school development team in formulating schoolprograms in accordance with the school's vision and mission. Theimplementation of TQM in learning uses media and learning methods that varyaccording to the RPP made by educators at the beginning of the school year andevaluates the TQM program through supervision by the principal and or seniorteacher appointed by the principal. The application of Islamic school culturecan be seen by mutual respect with teachers and fellow students, clean culture,mutual help, mutual cooperation and most importantly, the provision of variousIslamic religious knowledge in the form of yasinan recitation and religiouslectures. Constraints experienced internally by teachers who are lessprofessional, limited facilities and infrastructure, and communityparticipation/support factors. While the internal constraints are the lack ofenthusiasm for motivation from within the students and the factors of the familyenvironment that do not support the development of students at SMP N 1Labuhanhaji Timur.